Fabricação e validação de acessórios para espectroscopia e espectroeletroquímica usando impressão 3D para investigações de processos dinâmicos interfaciais e de superfícies - Silva Júnior, Joadir Humberto da (2021)
This work presents 3D printing as an auspicious additive manufacturing technique for several interesting applications to surface and interface spectroscopy, and to the coupling of electrochemical and spectroscopic techniques, proposing as utilities: the construction of a module for specular reflectance spectroscopy, and spectroelectrochemical cells (SEC) for UV-VIS absorption and Raman scattering in situ measurements. As a proof of concept, the reflectance module was used to obtain UV-VIS and mid-infrared reflection-absorption measurements of a film of the red dye Allura AC, showing the characteristic bands of the functional groups that make up the structure of this material, in line with the data described in the literature; The SECs were evaluated from spectroelectrochemical measurements related to the growth and electrochemically induced modification of Prussian Blue (PB) films on the surface of a platinum electrode. By maintaining the appropriate conditions, the growth of the PB film was accompanied by a proportional increase in the absorption signal at 700 nm in the UV-VIS region, related to the intervalence charge transfer between the Fe centers (Fe(II)-C for Fe(III)-N). Furthermore, measurements using the Raman SEC showed signs of inelastic scattering at 2092 and 2156 cm-1 - related to (CN) modes associated with Fe(II) and Fe(III) cations - during film growth. Then, the electrochemical conversion of the film to the Berlin Green (BG) and Prussian White (PW) forms was monitored by obtaining in situ spectra, whose profiles agree with those predicted and described in the literature. The conformity of the obtained results validates the built accessories and suggests many other applications, such as the study of kinetics and mechanisms of reactions/electrochemical processes, monitoring of short-lived species, and investigations of heterogeneities that are quite localized in surfaces or interfaces.